The place of artists' cinema : space, site and screen - Connolly, Maeve (Bristol : Intellect, 2009)
Introduction : the place of artists' cinema -- Between space, site and screen -- The place of the market -- Multi-screen projections and museum spaces -- Event-sites and documentary dislocations -- Cine-material screens and structures -- Conclusion : materials, places and social relations.
Includes bibliographical references and index.
boek